Quality assessment of clinical practice guidelines used in oral and maxillofacial surgery. Issue 3 (March 2020) - Madadian, M.A.; Benning, A.; Fan, K.; Pandis, N.; Seehra, J.
Abstract: An assessment of the quality of oral and maxillofacial surgery clinical practice guidelines is lacking. The aim of this investigation was to assess the quality of guidelines using the RIGHT (Reporting Items for practice Guidelines in HealThcare) checklist. The primary outcome was to assess the score (quality) of guidelines based on the RIGHT checklist and to identify predictors (region, type, single or multi-centre, and speciality/non-speciality) influencing the quality score. In this review, following a search of electronic databases and national society websites, a total of 25 guidelines were independently assessed by two assessors against the 22-item RIGHT checklist. Inter-assessor reliability was assessed. Deficiencies in the reporting of items relating to limitations, funding, declaration and management of interests, healthcare questions, and quality assurance were evident. The median overall score for the guidelines was 28 (range 14–66). Guidelines produced by multiple centres (β = 57.15, 95% confidence interval −26.62 to 87.68, P = 0.001, multivariate analysis) and non-speciality societies (β = 20, 95% confidence interval −0.03 to 40.03, P = 0.05, univariate analysis) tended to have higher quality scores. Overall, the quality of clinical practice guidelines used in oral and maxillofacial surgery was deemed suboptimal. If clinical practice guidelines are to be used in making treatment decisions for patients, clinicians should be aware of their possible limitations.